Legal support for sustainable development of rural areas in the Eurasian Economic Union states - Kuzmich, Iryna P. (Journal of the Belarusian State University. Law, 2024)
The article analyses the legal framework for sustainable development of rural areas in the Eurasian Economic Union states. The general key trends in the development of legislation have been identified, taking into account the historical background and peculiarities of the state agrarian policy. The author’s classification of legal models of ensuring sustainable development of rural territories is presented, the conclusion about the choice of the most optimal legal model of rural development for the Republic of Belarus is formulated.
Keywords: agrarian legislation; state agrarian policy; Eurasian Economic Union states; legal model; agriculture; rural areas; sustainable development